Developing Vocation Based Mathematics E- Module in Linear Program Material - Sumandya, I Wayan; Mahendra, I Wayan Eka (International Journal of Psychosocial Rehabilitation, 2020)
Vocation based Mathematics E-module is a modification from conventional module by elaborating the information technology utilization and vocation which was chosen by the students, it made this module become more interesting and interactive. This research aimed at obtaining high quality of e-module mathematics based on vocation from the side of validity, practical and affectivity. This used design research method with type research of developing which consist of three stages, i.e. preliminary research, prototyping and assessment. In stage of preliminary research, the data of needs analysis and material analysis. Prototyping stage was developing the product based on needs analysis and curriculum analysis. Assessment was assessing the product through expert validation, limited test and field test. The techniques used for collecting data was documentation, interview, questionnaires and test. Subject of this research was students of XI SMK in Badung Regency. According to the result of analysis, this research has successfully developed e-module of mathematics based on vocation in linear program material for XI class of Vocational School.